Philippine Health Sector Review - World Bank (Washington, DC, 2017)
The Philippines health sector is at a critical stage in its transformation. While the country has undertaken several significant health sector reforms in the past decades, a large unfinished policy agenda remains. The achievement of the health Millennium Development Goals (MDGs), especially among poor households, is at risk and there is a newly emerging challenge of addressing non-communicable diseases MDG. The overall health spending ratio is one of the lowest in the region with out-of-pocket (OOP) spending, a measure of financial protection, at over half of all health spending, well above the average for global comparators. It is within this context, that the Philippine health sector review takes stock of health reforms implemented to date, and evaluates the impact of these reforms on health systems performance. Based on this evaluation, the review identifies the challenges and future policy directions for accelerating the transformation of the Philippines health sector for improved health outcomes, financial protection of the population and consumer satisfaction.